REPRODUCIBILIDAD INTRAEXAMINADOR EN LA APLICACIÓN DEL SISTEMA INTERNACIONAL DE DETECCIÓN Y VALORACIÓN DE CARIES DENTAL (ICDAS II) (2009)
Objective: To assess intra-examiner reproducibility in the International Caries Detection and Assessment System (ICDAS II).Material and methods: A study of diagnostic reproducibility – agreement intra-examiner was done. An examiner evaluated 228 dental surfaces in 19 first semester students at the Dental School in the Santo Tomas University. The subjects’ teeth were cleaned by brushing and then examined. Scoring for lesion was done using a seven-category scale (0–6) according to the ICDAS criteria. The exams were done in two sessions at the same schedule. Weighted kappa values for intra-examiner reproducibility were calculated, both global and for all the individual ICDAS-II-codes.Results: The weighted Kappa values for the intra-examiner reproducibility were 0.7398. There was a Kappa value of 0.8455 in the 2B code (brown discoloration) and no agreement in the 1W code (first white change in enamel visible after 5 seconds air-drying) with a Kappa value of 0.0066.Conclusion: The intra-examiner reproducibility was considered good for the ICDAS criteria. Besides, there was a poor and a moderate agreement in the 1W and 2W scores, white opacity after air-drying and white opacity without air-drying, respectively. Further training is required to achieve a good reproducibility in every score.